Risk of cardiometabolic outcomes among women with a history of pelvic inflammatory disease: a retrospective matched cohort study from the UK - Kelvin Okoth; G. Neil Thomas; Krishnarajah Nirantharakumar; Nicola J. Adderley (BMC, 2023)
Abstract Introduction To describe the incidence and prevalence of pelvic inflammatory disease (PID) and to estimate the risk of cardiometabolic outcomes among women with PID compared to women without PID. Methods A UK retrospective matched cohort study using data from The Health Improvement Network. To assess cardiometabolic risk, women (aged ≥ 16 years) with PID were compared to matched controls without PID. Annual prevalence and incidence of PID (1998-2017) were estimated among women aged 16-50 years using annual cross-sectional and cohort analyses, respectively. Adjusted hazard ratios (aHR) and 95% CI for cardiometabolic outcomes were estimated using Cox proportional hazards models. The primary outcome was composite cardiovascular disease (CVD) and its subtypes, including ischaemic heart disease (IHD), heart failure (HF) and cerebrovascular disease. Secondary outcomes were hypertension, and type 2 diabetes mellitus (T2DM). Results Among the 715 recorded composite CVD events, the crude incidence rate per 1000 person-years was 1.5 among women with history of PID compared to 1.3 in matched controls. Compared to women without PID (N = 73,769), the aHRs for cardiometabolic outcomes among women with PID (N = 19,804) were: composite CVD 1.10 (95% CI 0.93-1.30); IHD 1.19 (95% CI 0.93-1.53); cerebrovascular disease 1.13 (95% CI 0.90-1.43); HF 0.92 (95% CI 0.62-1.35) hypertension 1.10 (95% CI 1.01-1.20); and T2DM 1.25 (95% CI 1.09-1.43). The prevalence (per 10,000 population) of PID was 396.5 in 1998 and 237 in 2017. The incidence (per 10,000 person-years) of PID was 32.4 in 1998 and 7.9 in 2017. Conclusion There was no excess risk of composite CVD or its subtypes among women with history of PID compared to matched controls. Findings from our study suggest that history of PID was associated with an increased risk of hypertension and type 2 diabetes mellitus, two major risk factors for CVD. Additional studies are required to support these findings.